Egg white-derived peptides prevent male reproductive dysfunction induced by mercury in rats. (February 2017) - Rizzetti, Danize Aparecida; Martinez, Caroline Silveira; Escobar, Alyne Goulart; da Silva, Taiz Martins; Uranga-Ocio, José Antonio; Peçanha, Franck Maciel; Vassallo, Dalton Valentim; Castro, Marta Miguel; Wiggers, Giulia Alessandra
Abstract: Oxidative stress in known to contribute to the male reproductive dysfunction induced by mercury (Hg). Our study tested the hypothesis that the egg white hydrolysate (EWH), a potent antioxidant in vitro, is able to prevent the effects of prolonged Hg exposure on male reproductive system in rats. For this, rats were treated for 60 days with: a) Untreated - saline solution ( i.m. ); b) Hydrolysate - EWH (1 g/kg/day, gavage); c) Mercury - HgCl2 (1st dose 4.6 μg/kg, subsequent doses 0.07 μg/kg/day, i.m. ); d) Hydrolysate-Mercury. At the end of the treatment, sperm motility, count and morphological studies were performed; Reactive Oxygen Species (ROS) levels, lipid peroxidation, antioxidant capacity, histological and immunohistochemical assays on testis and epididymis were also carried out. As results, HgCl2 -treatment decreased sperm number, increased sperm transit time in epididymis and impaired sperm morphology. However, these harmful effects were prevented by EWH. HgCl2 -treatment also increased ROS levels, lipid peroxidation and antioxidant capacity in testis and epididymis as well as promoted testicular inflammation and histological changes in epididymis. EWH improved histological and immunohistochemical alterations, probably due to its antioxidant property. In conclusion, the EWH could represent a powerful natural alternative to protect the male reproductive system against Hg-induced sperm toxicity. Highlights: Mercury exposure affects sperm quality and promotes male reproductive dysfunction. Mercury increases oxidative and inflammatory factors on male reproductive system. Bioactive peptides from egg white prevent the damage on male reproductive system. These effects are related to their antioxidant and anti-inflammatory properties.